2020
DOI: 10.1152/physiolgenomics.00059.2020
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of the IGF hormones and IGF binding proteins across time and tissues in a model reptile

Abstract: The Insulin and Insulin-like Signaling (IIS) network regulates cellular processes including pre- and post-natal growth, cellular development, wound healing, reproduction, and longevity. Despite their importance on the physiology of vertebrates, the study of the specific functions of the top regulators of the IIS network - insulin-like growth factors (IGFs) and IGF binding proteins (IGFBPs) has been mostly limited to a few model organisms. To expand our understanding of this network, we performed quantitative g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…The development and maintenance of skeletal muscle is also regulated by both endocrine and autocrine secretion of IGFBPs, such that serum concentrations generally correlate negatively with muscle mass (Lang et al, 2003). Beatty and Schwartz (2020) also show that IGFBP expression is ubiquitous across both tissue type and developmental stage in the lizard Anolis sagrei, an important step in expanding our understanding of these mechanisms to other animal taxa. Finally, IGFBPs also have effects independent of IGFs through a variety of poorly understood processes (Clemmons, 2018).…”
Section: Ils and Mtormentioning
confidence: 81%
“…The development and maintenance of skeletal muscle is also regulated by both endocrine and autocrine secretion of IGFBPs, such that serum concentrations generally correlate negatively with muscle mass (Lang et al, 2003). Beatty and Schwartz (2020) also show that IGFBP expression is ubiquitous across both tissue type and developmental stage in the lizard Anolis sagrei, an important step in expanding our understanding of these mechanisms to other animal taxa. Finally, IGFBPs also have effects independent of IGFs through a variety of poorly understood processes (Clemmons, 2018).…”
Section: Ils and Mtormentioning
confidence: 81%
“…In theory, expression of housekeeping genes should be consistent between individuals, regardless of treatment, because they are required for normal cellular function. We used two of the most common housekeeping genes, GAPDH and EEF2, in this study; however, because there is evidence from mice that GAPDH in particular is not a stable reference gene under caloric restriction (Gong et al, 2016), we controlled for the eventuality that neither gene might be appropriate for normalizing our expression data by randomizing samples at RNA isolation, cDNA synthesis and qPCR steps to disperse technical error amongst treatments, as well as normalizing RNA amounts when making cDNA (Beatty and Schwartz, 2020). Indeed, we found that expression levels of GAPDH and EEF2 differed between treatments, both when accounting for final body mass (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time quantitative PCR (qPCR) was conducted as described in Beatty and Schwartz (2020) to quantify IGF1, IGF2, GAPDH and EEF2 in a multiplex qPCR reaction containing 1× PrimeTime Gene Expression Mastermix (Integrated DNA Technologies DNA, 1055772), 0.3 µmol l −1 of each primer, 0.2 µmol l −1 of each probe, 3 µl of cDNA at a 1:100 dilution in a final volume of 20 µl volume. Samples were randomized to 2 plates and run in triplicate reactions on a BioRad CFX96 qPCR thermal cycler: 3 min 95°C initial activation, 2-step amplification cycle of 15 s at 95°C and 1 min at 60°C, repeated for 45 cycles.…”
Section: Igf Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although humans also express the paralogous hormone IGF2 at high levels as adults, [ 51 ] biomedical rodent models do not, [ 52 ] resulting in this hormone being understudied in the context of senescence. Recent studies demonstrate that reptiles and birds express IGF2 at high levels in adulthood, [ 53,54 ] similar to humans, providing new model systems to study the physiological effects of this hormone in adulthood.…”
Section: Evolutionary Biology Influences Physiologymentioning
confidence: 99%